Impact of Informal Human Resource Practices on Employee Outcomes in Private Tertiary Education Institutions - Saruchera, Sibonginkosi; Gie, Liiza (International Journal of African Higher Education, 2025)
This article examines the impact of informal human resource practices on academic turnover, performance deterioration, absenteeism, and a decline in employee development in private tertiary education institutions. It proposes a formal human resource management model for private tertiary education institutions based on a mixed-methods approach, through which the researcher concurrently collected quantitative data using a questionnaire and qualitative data using structured interviews. Combined purposive sampling and stratified sampling produced 171 academic questionnaire responses and eight human resources business partners' online interviews. The study found that career development and growth, working conditions and work-life balance, performance management and recognition, recruitment and selection, employee training and development, and remuneration contributed to the key challenges faced by private tertiary education institutions. Adopting a formal human resource management model may enhance academic performance, employee development, reduce absenteeism, and retain academic staff while improving their institutional reputation as both an employer and a preferred choice for students.